Intermittent hypoxic training at lactate threshold intensity improves aiming performance in well-trained biathletes with little change of cardiovascular variables - Czuba ,M.; Bril, G.; Ploszczyca, K.; Piotrowicz, Z.; Chalimoniuk, M.; Roczniok, R.; Zembron-Lacny, A.; Gerasimuk, D.; Langfort, J. (BioMed Research International, 2019)
The main objective of this research was to evaluate the efficacy of intermittent hypoxic training (IHT) on aiming performance and aerobic capacity in biathletes. Fourteen male biathletes were randomly divided into a hypoxia group (H) (n . 7), which trained three times per week in a normobaric hypoxic environment (FiO2 .16.5%, 2000m a.s.l.) with lactate threshold intensity (LT) determined in hypoxia, and a control group (C) (n . 7), which exercised under normoxic conditions with LTintensity determined in normoxia. The training program included three weekly microcycles, followed by three days of recovery. The main part of the interval workout consisted of four 7 min (1st week), 8 min (2nd week), or 9 min (3rd week) running bouts at treadmill separated by 2 minutes of active recovery. After the warm-up and during the rest between the bouts, the athletes performed aiming to the target in the standing position with a sporting rifle (20 s). The results showed that the IHT caused a significant (p < 0.05) increase in retention time in the target at rest (RT9rest) by 14.4% in hypoxia, whereas RTpostincremental test (RT9post) increased by 27.4% in normoxia and 26.7% in hypoxia. No significant changes in this variable were found in group C. Additionally, the capillary oxygen saturation at the end of the maximal effort (SO2capillary max) in hypoxia increased significantly (p < 0.001) by ¡4% after IHT. The maximal workload during the incremental test (WRmax) in normoxia also increased significantly (p < 0.001) by 6.3% after IHT. Furthermore, in absolute and relative values of VO2max in normoxia, there was a propensity (p < 0.07) for increasing this value by 5% in group H. In conclusion, the main findings of this study showed a significant improvement in resting and postexercise aiming performance in normox